On leading in times of change - Rush, Stephen 1954- (Center for Creative Leadership, 2012)
The ongoing state of many contemporary organizations is one of change. The pace and complexity of change contribute to intense emotions that play out both inside and outside organizations. The leader's challenge in dealing with change is to recognize and understand the patterns of response that people express as they learn their way through transition and to customize intervention strategies that help individuals move forward in the changing environment. This collection of sixteen pieces-written by the Center for Creative Leadership's highly experienced and knowledgeable faculty members and re.
Includes bibliographical references and index. - Print version record
Keywords: Leadership; Executive ability; Organizational change; Organizational Innovation; Aptitude pour la direction; Changement organisationnel; BUSINESS & ECONOMICS; Leadership